Factors affecting effectiveness of enforcement handling drug abuse in Dungun, Terengganu / Mohd Ridhuan Ismail - Ismail, Mohd Ridhuan (2020)
Drug abuse is a complex issue and has been a serious public health problem in Malaysia. The power to investigate and seize is granted to the police in the course of investigation. The main agencies of enforcement, PDRM and NCID are responsible in preventing drug trafficking. The research conducted to determine the factors affecting the effectiveness of enforcement handling drug abuse; staff commitment, equipment and facilities and frequency of operation. These three factors will be examine in order to find the affect that may influence the enforcement effectiveness towards drug abuse. A total of200 respondents involving enforcement agencies in Dungun were chosen by applying a sampling technique data questionnaire of quantitative method. A structured questionnaire will be used to elicit responses from the agencies involved using a convenience sampling techniques. Drug were used in medication, Research and Development (R&D) and as a preventive medicine to cure illness and diseases. Enforcement play an important role in keeping the safety and harmony of a country. People have to cooperate with enforcement and to not discriminate people regarding their background. The knowledge and awareness of drug abuse are commercially acknowledged by communities in Malaysia. The research had shown there are a significant relationship between the factors affecting enforcement effectiveness handling drug abuse.